Space-charge limiting current of charged-particle beam in coaxial drift tube with dielectric inserts in strong axial magnetic field - Yatsenko, T.; Sotnikov, G.V.; Ilyenko, K. (Вопросы атомной науки и техники, 2013)
We obtain an analytical estimate of space-charge limiting (SCL) current of relativistic charged-particle beam propagating in infinitely long grounded coaxial drift tube with dielectric inserts in the strong magnetic field approximation. The received analytical estimate is compared with numerical calculations of SCL current.